2002
DOI: 10.1074/jbc.m110008200
|View full text |Cite
|
Sign up to set email alerts
|

A Lipid-regulated Docking Site on Vinculin for Protein Kinase C

Abstract: During cell spreading, binding of actin-organizing proteins to acidic phospholipids and phosphorylation are important for localization and activity of these proteins at nascent cell-matrix adhesion sites. Here, we report on a transient interaction between the lipid-dependent protein kinase C␣ and vinculin, an early component of these sites, during spreading of HeLa cells on collagen. In vitro binding of protein kinase C␣ to vinculin tail was found dependent on free calcium and acidic phospholipids but independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 79 publications
1
69
0
1
Order By: Relevance
“…Therefore, we tested in vitro PKC␣ binding to FLN domain constructs after preincubation with phospholipid vesicles, using a protocol that has been applied previously in our laboratory to analyze PKC binding to vinculin (44). To map filamin binding sites in dot overlay assays, deletion constructs of the N and C terminus were generated from human FLNa cDNA by PCR and cloned into expression vectors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we tested in vitro PKC␣ binding to FLN domain constructs after preincubation with phospholipid vesicles, using a protocol that has been applied previously in our laboratory to analyze PKC binding to vinculin (44). To map filamin binding sites in dot overlay assays, deletion constructs of the N and C terminus were generated from human FLNa cDNA by PCR and cloned into expression vectors.…”
Section: Methodsmentioning
confidence: 99%
“…Characterization of PKC Binding Properties-PKC ligand binding can involve a complex interplay of protein-protein and protein-lipid interactions, as exemplified by its ligands syndecan 4 (45) or vinculin (44). To identify the main characteristics of the interaction with filamin, domain constructs of the lipid and Ca 2ϩ -binding PKC regulatory domain (rd), the variable hinge region (V3), that is involved in intercellular targeting (46), and ligand binding (9), and the kinase domain (kd) were employed in overlay assays.…”
Section: The Interaction Of Flna Constructs [N1-4] and [22-24c] Witmentioning
confidence: 99%
“…In vitro studies as well as in vivo studies in several cell types have described both tyrosine and serine phosphorylation sites on the vinculin molecule (37,38). There is evidence that phosphorylation at the Tyr 1065 site near the C terminus of the tail domain affects cell traction and spreading and the dynamics of the incorporation of vinculin into focal adhesions (37,39,40).…”
mentioning
confidence: 99%
“…It thus serves a regulatory, dynamic linkage between the ECM and intracellular actin cytoskeleton. It was demonstrated that acidic phospholipids inhibit intramolecular association between the N-and C-terminal regions of vinculin, exposing actin-binding and protein kinase C phosphorylation sites on serines 1033 and 1045 [34,35]. Upon activation of hmeprina ⁄ b in stably transfected MDCK cells, the 116 kDa full-length form of vinculin and truncated forms (75 and 85 kDa) were detected in cell culture supernatants (Fig.…”
Section: Establishment Of a Simple 2d Ief/sds/ Page-based Protease Prmentioning
confidence: 99%
“…Those half-cleaved products are most probably related to in-gel digestion artefacts because cleavage within this protein sequence stretch by meprin must be excluded due to an overall amino acid sequence coverage of this protein that exceeded amino acid 182. In addition, the two half-cleaved peptides DQAVSDTELQEMSTEGSK (residues [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and DTELQEMSTEGSK (residues 28-40) in SSP 502 and 1502 were chromatographically separated and were not in-source fragmentation products generated during the ionization process. The former peptide represented the mature N-terminus of clusterin (aspartate at position 23) and hence was not generated by meprin activity.…”
Section: Protein Identification By Means Of Lc-ms/ms Phenyx-based Anmentioning
confidence: 99%